تحليل هيدروغراف الجريان القاعدي لنبع السن في الساحل السوري - حايك, شريف; عبد الرحمن, عباس (Latakia University Journal -Engineering Sciences Series, 2018)
يتشكل نبع السن عند أقدام الجبال الساحلية ويصبّ في البحر المتوسط قرب قرية عرب الملك. وتُستخدم مياهه حالياً لأغراض الشرب والري والصناعة، ويذهب ما يفيض منه إلى البحر. يهدف البحث إلى تحديد مدى استجابة غزارة النبع اليومية للهطولات المطرية اليومية، وإيجاد معادلة تصريف الانحسار للتنبؤ بمعدلات تصريف النبع وحجوم الجريان بعد أي زمن محدد من بداية الجريان القاعدي للنبع، الأمر الذي يسمح بإدارة واستثمار الموارد المائية المتاحة من خلال التصميم الأمثل لمآخذ المياه من الينابيع بشكل عام. تترلوح استجابة غزارة نبع السن اليومية بين (3-5) يوم أيام للهطولات المطرية اليومية المتقطعة المتوسطة والغزيرة الشدة نسبياً. فتسبب زيادة لغزارة النبع تتراوح بين (0.5-1 m3/sec). ويميل التصريف السنوي للنبع إلى الانخفاض بمعدل 0.0975 m3/sec وذلك خلال الفترة (1974-2016)م. بينما خلال فترة (2016-1994) تزداد قيمة التصاريف الشهرية الأصغرية بمقدار 0.1284 m3/sec، وتنخفض قيمة التصاريف الشهرية الأعظمية بمقدار 0.0752 m3/sec. لقد تم التمكّن من وضع معادلة لتصريف الانحسار لنبع السن بالشكل: . يُوصى باعتماد تحليل منحنيات الانحسار في الينابيع للتنبؤ بالتصريف الأمثل لها خلال أزمنة محددة. AlSin Spring spurts at the foot of coastal mountains and pours in The Mediterranean sea near Arab-Almulk village. Presently, spring water used for drinking, irrigation and industry, while excess water goes to sea. Current research aims to determine the daily discharge response to daily rainfall, and to set an equation for recession discharge for predicting spring discharge and volumes of flow after definite time from the beginning of spring base flow, which allows to operate and manipulate available water resources through an optimum design of water intake from this spring. Response time of AlSin Spring between (3-5) days for average discrete daily rainfall with high intensity which caused 0.5 ~ 1.0 m3/sec increasing in spring discharge value. Yearly discharge trends to decrease with a rate of 0.0975 m3/sec between 1974 and 2016 years. While the monthly minimum discharges increase about 0.1284 m3/sec, and monthly maximums decrease about 0.0752 m3/sec between 1994 and 2016. We estimate a formula for receding discharge of AlSin Spring as follow : We recommend adopting recession curve analysis to predict the optimal discharge of springs within definite periods.